Relationship of the quality of life in capecitabine-treated colorectal cancer patients to sociodemographic characteristics and drug-related adverse effects - A. Sabry, Shelan; J. Ibrahem, Mazin; Jabarah, Mohammed A. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Colorectal cancer (CRC) is the third most prevalent cancer worldwide with 1.80 million new cases and 862,000 deaths in 2018. Depending on the stage, upfront surgery is the main form of treatment, followed by adjuvant chemotherapy. Many drugs were approved by the U.S. Food and Drug Administration for the treatment of CRC, one of which is Capecitabine. During cancer treatment, patient-reported symptoms and quality of life parameters can provide additional information to evaluate and compare the efficacy and toxicity of the treatments. Despite the importance of this issue, there is no published data that evaluates this vital parameter in Iraqi patients receiving anti-cancer drugs, in general, or those on Capecitabine, in particular. Objective: To evaluate the relationship between quality of life in capecitabine-treated colorectal cancer patients and their sociodemographic characteristics as well as drug-related adverse effects. Methods: A cross-sectional, open-label study was conducted at Al-Amal and Oncology Teaching Hospitals in Baghdad during the period from November 2021 to June 2022. A convenient sampling method was adopted to enrol patients in the current study. Quality of life assessment was performed using the European Organization for Research and Treatment of Cancer quality of life questionnaire (QLQ-C30). Microsoft Excel 2019 and the Statistical Package for the Social Sciences (SPSS, Version 25) were used for data entry and analysis. The descriptive analysis focused on frequencies and percentages. Continuous variables were presented as (mean ± Standard Deviation). Categorical data were presented as proportions and the Chi-squared test was used to study the associations between variables. The level of significance was considered at P≤0.05. Results: A total of 102 patients were enrolled in the current study. Generalized fatigue was the most common adverse event (63.7%) of participants. Only 6.9% of participants had abnormal renal function tests. Some capecitabine-treated patients had good quality of life, others did not. Conclusion: The quality of life of capecitabine-treated colorectal cancer patients seems to be sensitive to their sociodemographic characteristics and adverse effects of the drug